Representation matters: shaping future medical enrichment and pipeline programs for students in a post-pandemic world - Mukarram, Muhammad B.; Ramirez, Mayra Lucas; Favors, Nakeisha; Takele, Rebecca; Scotland, Kymora B. (Frontiers in Education, 2026)
The COVID-19 pandemic significantly limited access to Science, Technology, Engineering, and Mathematics (STEM) pipeline and enrichment opportunities for all students, but the impact was particularly profound for those historically underrepresented in these fields. These students often face structural barriers such as limited prior exposure to STEM, fewer mentorship opportunities, and socioeconomic challenges that restrict entry into STEM pathways. Given these barriers, securing continued access to pipeline programs during the pandemic was especially critical to maintain equity in STEM education. To contribute to the growing research base focused on evaluating the effectiveness of virtual and/or hybrid STEM enrichment programs, our team conducted a retrospective cohort study of a hybrid program led by the senior author, and hosted by the University of California Los Angeles (UCLA) Department of Urology and the Ernest Everett Just Youth Science Program by the Bridge Builders Foundation in February 2022. In this program, twenty-four middle school and high school students participated in three separate 45-min interactive virtual lectures focused on general anatomy, the cardiovascular system, and the gastrointestinal system, along with an in-person dissection lab. Pre- and post-program surveys were completed by the students to assess their confidence in their abilities, their attitudes toward medical careers, and if they felt the medical field had a place for people of their background. Of the 24 participants, 63% identified as Black or African American and 16% identified as Latinx or Hispanic. Following the program, there were no statistically significant differences in students perceptions of their academic abilities or connectivity with physicians and medical students. However, there were noticeable differences in students’ survey responses, as well as in their excitement during the program. In the post-COVID-19 era, medical school programs and STEM programs focused on medicine should consider fully virtual and hybrid medical enrichment initiatives as a medium of positively encouraging middle school and high school students to pursue careers in medicine.